The Unintended Consequences of Meritocratic Government Hiring - Athanasios Geromichalos; Ioannis Kospentaris (University of California, Department of Economics, 2020)
In an attempt to mitigate the negative effects of clientelism, many governments around the world have adopted meritocratic hiring of public employees. This paper challenges the effectiveness of this common practice by showing that meritocratic government hiring can have unintended negative consequences on macroeconomic aggregates. In many countries, public employees enjoy considerable job security and generous compensation schemes; as a result, many talented workers choose to work for the public sector, which deprives the private sector of productive potential employees. This, in turn, reduces firms' incentives to create jobs, increases unemployment, and lowers GDP. To quantify the effects of this novel channel, we extend the standard Diamond-Mortensen-Pissarides model to incorporate workers of heterogeneous productivity and a government that fills public sector jobs based on merit. We calibrate the model to aggregate data from Greece and perform a series of counterfactual exercises. We find that the adverse effects of our mechanism on the economy's TFP, GDP, and unemployment are sizable.
Keywords: E24; J30; J45; J64; 330; search and matching models; public sector; meritocracy; unemployment